Does maxillary sinus proximity affect molar root resorption during distalization using Invisalign? a CBCT study - Dina Elfouly; Nadia M. El-Harouni; Hanan A. Ismail; Tarek El-Bialy; Ahmed Ghoneima (BMC, 2023)
Abstract Background This study aimed to assess the correlation between maxillary sinus proximity to root apices of maxillary molars and root resorption during molar distalization using clear aligner therapy (CAT). Materials and methods Thirty-eight cone beam computed tomography scans (CBCTs) obtained pre- (T0) and post-treatment (T1) from 19 adult patients (36.68 ± 13.50 years), who underwent maxillary molar distalization using Invisalign® aligners (Align Technology, Inc., San José, CA, USA) with a minimum of 2 mm distalization, were evaluated in this study At least 22 h of aligner wear per day was a main inclusion criterion. Sinus proximity and changes in root lengths were measured for 61 molars (183 roots). Spearman coefficient analysis was used for assessing correlation between sinus proximity and root resorption. The level of significance was set at p ≤ 0.05. The reproducibility of measurements was assessed by intraclass correlation coefficient (ICC). Results Spearman coefficient revealed no significant correlation between sinus proximity and molar root resorption for mesiobuccal, distobuccal or palatal roots (p = 0.558, p = 0.334, p = 0.931, respectively). Conclusion There was no correlation between maxillary sinus proximity to root apices of maxillary molars and root resorption.